The Effect of CAM Methods Plan to Apply by Pregnant Women in Order to Cope with Birth Pain on Fear of Childbirth and Childbirth Self-Efficacy - Barut, Sümeyye; Okyay, Esra Karataş (My University, 2023)
Objective: In the study, it was aimed to determine the effect of CAM methods planned to be used by pregnant women in order to cope with birth pain on fear of childbirth and childbirth self-efficacy Material-Method: The cross-sectional study was completed with 455 pregnant women. The study data were collected through Identifying Information Form, which also aimed to determine CAM methods planned to be used, The Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) Version A, and Childbirth Self-Efficacy Inventory (CBSEI). Results: In the study, it was determined that the pregnant women planned to use mind-body based CAM methods by 31.4%, manipulative and body-based methods by 25, biologically based methods by 1.1%, energy therapy methods by 0.9%, and alternative medicine methods by 0.7%. In addition, it was determined that there was a significant difference between CBSEI efficacy and outcome expectancy subscales mean scores and CBSEI total scale mean score of the pregnant women who did not plan to apply CAM methods to reduce their labor pain compared to those who planned to use these methods. Conclusion: It was found in the study that the pregnant women planned to use mind-body based methods the most in order to cope with labor pain in childbirth. It was also determined that there was no significant difference between the groups in terms of fear of childbirth according to their planning to use CAM methods to cope with labor pain in childbirth, and that childbirth self-efficacy levels of those who planned to use CAM methods were significantly low.
Keywords: Pregnancy; Traditional Medicine; Fear of Childbirth; Self-Efficacy.